Collagen-like Motifs of SasG: A Novel Fold for Protein Mechanical Strength. Issue 6 (15th March 2023) - Bruce, Alexander J.E.; Paci, Emanuele; Brockwell, David J.
Graphical abstract: Highlights: The structural determinants of the high unfolding force for SasG are unclear. Structural, thermodynamic and mechanical effects of 18 variants investigated. Variants' ϕ-values show importance of mechanical clamp and domain interface motifs. Study identifies and characterises collagen-like regions as a novel mechanical motif. Abstract: The Staphylococcus aureus surface protein G (SasG) is associated with host colonisation and biofilm formation. As colonisation occurs at the liquid-substrate interface bacteria are subject to a myriad of external forces and, presumably as a consequence, SasG displays extreme mechanical strength. This mechanical phenotype arises from the B-domain; a repetitive region composed of alternating E and G5 subdomains. These subdomains have an unusual structure comprising collagen-like regions capped by triple-stranded β -sheets. To identify the determinants of SasG mechanical strength, we characterised the mechanical phenotype and thermodynamic stability of 18 single substitution variants of a pseudo-wildtype protein. Visualising the mechanically-induced transition state at a residue-level by ϕ -value analysis reveals that the main force-bearing regions are the N- and C-terminal 'Mechanical Clamps' and their side-chain interactions. This is tailored by contacts at the pseudo-hydrophobic core interface. We also describe a novel mechanical motif – the collagen-like region and show that glycine to alanine substitutions, analogous to those found in Osteogenesis Imperfecta (brittle bone disease), result in a significantly reduced mechanical strength.